Qualidade de batata cv. Agata influenciada por diferentes concentrações de adubação potássica - Furlaneto, Karina Aparecida [UNESP]; Lima, Pedro Fernades Fleury de Souza [UNESP]; Daiuto, Érica Regina [UNESP]; Job, Andre Luiz Gomes [UNESP]; Mendonça, Veridiana Zocoler de [UNESP]; Vieites, Rogério Lopes [UNESP]; Carvalho, Lídia Raquel de [UNESP] (My University, 2014)
It was evaluated physical and chemical parameters of potato cv. Agata, type 2 quality, submitted to different concentrations of potassica fertilization. The concentrations used KCl were 0, 100, 200 and 400 applied 100% in the planting and 100, 200 and 400 applied 50% in the planting and 50% covering. The tubers were appraised every 2 days, for 14 days, to verify the weight loss and to the 0 and 14 days for hidrogenionic potential, tritabel acidity, soluble solids, sugars reducers and starch content. The different doses of KCl didn't influence in the tubers weigth loss. For the pH values, tritable acidity and sugars reducers there was not difference among the treatments, just for the days of storage. The treatments in that it was applied 400 of KCl the 100% in the planting and 200 and 400 applied 50% in the planting and 50% covering, they showed the smallest values of SS. The treatments control, 100 and 200 applied 100% in the planting had inferior averages of starch on the 0 in relation to the other treatments. In function of the you analyze accomplished, the content of 200 of applied KCl 50% in the planting and 50% covering would be the more recommended for the cultivation of the potato cv. Agata, 12.

Avaliou-se parâmetros físico-químicos na qualidade de batata cv. Agata, tipo 2, submetidas a diferentes concentrações de adubação potássica. As concentrações de KCl utilizadas foram 0, 100, 200 e 400 aplicadas 100% no plantio e 100, 200 e 400 aplicadas 50% no plantio e 50% cobertura. Os tubérculos foram avaliados a cada 2 dias, durante 14 dias, para verificar a perda de massa e aos 0 e 14 dias analisou-se o potencial hidrogeniônico, acidez titulável, sólidos solúveis, açúcares redutores e teor de amido. As diferentes doses de KCl não influenciaram na perda de massa dos tubérculos. Para os valores de pH, acidez titulável e açúcares redutores não houve diferença entre os tratamentos, apenas em relação aos dias de armazenamento. Os tratamentos em que se aplicou 400 de KCl 100% no plantio e 200 e 400 aplicadas 50% no plantio e 50% cobertura , mostraram os menores valores de SS. Os tratamentos controle, 100 e 200 aplicados 100% no plantio tiveram médias inferiores de amido no dia 0 em relação aos demais tratamentos. Em função das analises realizadas, a dose de 200 de KCl aplicadas 50% no plantio e 50% cobertura seria a mais recomendada para o cultivo da batata cv. Ágata, 12.
Quality of batata cv. Agata influenced by different levels of potassim fertilization
Keywords: Solanum tuberosum L.; Postharvest; Starch; Sugar; Solanum tuberosum L.; Pós-colheita; Amido; Açúcares